La politique polonaise à la lumière des rapports diplomatiques belges (1939-1945) - Łaptos, Józef; Goddeeris, Idesbald; Grosbois, Thierry; Kawka, Inga; Prażuch, Wojciech; Szczur, Przemysław (2021)
"This volume highlights Belgian diplomacy from a European perspective. A group of Polish and Belgian historians came up with the idea of bringing together Belgian dispatches and diplomatic reports devoted to the efforts that the Poles made during the Second World War to regain the independence of their state, which had fallen victim of German and Soviet aggression. The result - 275 duly annotated documents - allows us to retrace Belgian reaction to the Polish resistance, armed struggle and diplomatic initiatives, including the idea of a Central European federation. The attitude toward the Polish disappointment caused by the British and American concessions to the USSR as well as by the catastrophic failure leading to the sovietization of Poland, is quite revealing: it shows the political, intellectual, even emotional framework of the Belgian circles in exile, but also the sources of Belgium's Atlantic commitment and its tireless support for supranational groupings." – Abstract, page 492